2021
DOI: 10.1093/petrology/egab061
|View full text |Cite
|
Sign up to set email alerts
|

Meter-Scale Chemical and Isotopic Heterogeneities in the Oceanic Mantle, Leka Ophiolite Complex, Norway

Abstract: Mantle peridotites from three 3 x 3 metre grids sampled at kilometer distances from one another in the ca. 497 Ma Leka Ophiolite Complex (LOC), Norway, are examined in order to investigate the chemical and isotopic nature of oceanic mantle domains at the cm- to km-scale. The lithology of each grid locality is predominantly harzburgite, but includes layers and lenses of dunite and pyroxenite. Major and lithophile trace element compositions indicate a history of prior melting at pressures at or slightly below th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…constraints, harzburgites and dunites from the same pair were not always collected in close proximity (3-20 m separation) (Table 1). As shown by tightly spaced sampling of other ophiolites (Haller et al, 2021;OʼDriscoll et al, 2018;Snortum & Day, 2020) large Os isotope variations can occur between harzburgites separated by a few meters or even centimeters. The relatively large separation between each dunite and its paired harzburgite thus implies that the compositions of the harzburgites do not necessarily represent those of the harzburgites parental to the associated dunites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…constraints, harzburgites and dunites from the same pair were not always collected in close proximity (3-20 m separation) (Table 1). As shown by tightly spaced sampling of other ophiolites (Haller et al, 2021;OʼDriscoll et al, 2018;Snortum & Day, 2020) large Os isotope variations can occur between harzburgites separated by a few meters or even centimeters. The relatively large separation between each dunite and its paired harzburgite thus implies that the compositions of the harzburgites do not necessarily represent those of the harzburgites parental to the associated dunites.…”
Section: Resultsmentioning
confidence: 99%
“…This model is unavoidably speculative, as it is based on a small number of samples. As several studies have shown (Haller et al, 2021;OʼDriscoll et al, 2018;Snortum & Day, 2020), large heterogeneities in Os isotopic composition and HSE abundances can exist on length scales of a meter or less in ophiolites. Therefore, drawing conclusions from a few widely spaced samples may be unwise.…”
Section: Batin Dunite Formationmentioning
confidence: 99%
“…Tick marks indicate 5% melting increments. Also plotted are the ophiolitic peridotites from the settings of ocean‐continent‐transition (OCT; data from Becker et al., 2006; Fischer‐Gödde et al., 2011; Lorand et al., 1999, 2000, 2008, 2010; Luguet et al., 2007; Rampone et al., 1995; Reisberg & Lorand, 1995; Riches & Rogers, 2011; Saal et al., 2001; Snow et al., 2000; van Acken, Becker, Hammerschmidt, et al., 2010; van Acken, Becker, Walker, et al., 2010; van Acken et al., 2008; Wang et al., 2013), mid‐ocean‐ridge (MOR; data from Aldanmaz et al., 2012; Batanova et al., 2008; Dijkstra et al., 2010; Gong et al., 2020; Hanghøj et al., 2010; Hu et al., 2020; Schulte et al., 2009; Sergeev et al., 2014; Uysal et al., 2012) and supra‐subduction‐zone (SSZ; data from Agranier et al., 2007; Aldanmaz et al., 2012, 2020; Büchl et al., 2002, 2004; Chen et al., 2020; Haller et al., 2021; C. Z. Liu et al., 2018; O'Driscoll et al., 2012, 2015, 2018; Prelević et al., 2015; Secchiari, Gleissner, et al., 2020; Snortum & Day, 2020; Uysal et al., 2012; Xu & Liu, 2019). Arrows show the possible additional processes to account for the data.…”
Section: Discussionmentioning
confidence: 99%
“…HSE systematics and Re‐Os isotopes further support the conclusion that the Lesvos ophiolite was formed in an OCT environment: (a) Most of the Lesvos lherzolites have PUM‐like HSE patterns (Figure 4) and plot in the modeled near‐fractional partial melting trend (Figure 5), both of which can well match their relatively fertile “Alpine” character coupled with low degrees of melt extraction (Koglin et al., 2009); (b) with regards to absolute and relative HSE abundances and Re‐Os isotopic compositions (Figures 5–7), almost all the Lesvos peridotites fall within the field of the OCT and MOR peridotites, but mostly within the OCT field, indicating that the Lesvos peridotites have not experienced subduction‐related processes, in contrast to the SSZ setting of most Mesozoic ophiolites exposed in the Eastern Mediterranean Tethyan region (A. H. F. Robertson, 2002); (c) given that the impact of melt‐rock interaction on 187 Os/ 188 Os ratios is relatively limited (see Section 5.2.1), it is more likely that the near‐horizontal 187 Os/ 188 Os versus Al 2 O 3 variation of the Lesvos peridotites, especially the depleted harzburgites (Figure 7) was due to recent melt depletion during rifting and thinning of the Lesvos lithosphere (Koglin et al., 2009), along with the continuous creation of oceanic lithosphere by an incipient Neo‐Tethyan rift; (d) the ancient T RD age (1.6 Ga) of sample 17AC09 can reflect the mantle Os‐isotope heterogeneity of the type observed in other oceanic lithosphere (e.g., Brandon et al., 2000; Haller et al., 2021; Harvey et al., 2006; C. Z. Liu et al., 2008). Focusing on the Alpine‐Apennine peridotites typical for the OCT setting, McCarthy and Müntener (2015, 2019) have argued that those ancient and variably depleted, refractory domains might be previously recycled into convective mantle and subsequently exhumed during continental breakup and rifting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation